Rancang Bangun Aplikasi Penerimaan Siswa Baru Berbasis Web (Studi Kasus: Intersky Study Surabaya) - Robiyanto, Robiyanto; Jusak, Jusak; Churniawan, Agus Dwi (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2017)
Intersky Study Surabaya is a flight attendant school education and training branch of Intersky Study Balikpapan. The existing problems in Intersky Study Surabaya occurs when the registration process is found there is a loss of data registries result is not stored properly, then the delay in receipt of due process of sending data to the central office in Balikpapan, then in the selection process of registration occurs vote repeatedly performed in Intersky Study Surabaya also Intersky Study conducted in Balikpapan. And last is the problem ease of registration for applicants outside the area that does not allow the applicant to come directly to Intersky Study Surabaya. Solutions offered to help with these problems is an admissions application that comes Analytical Hierarchy Process (AHP) which can process data registration and may provide direct student enrollment announcement. Based on this research can be concluded that the final project, had managed to make the application of new admissions to assist in data processing registrant and help in the decision of admission according to user needs Intersky Study Surabaya